Controlled Multilingual Thesauri for Kazakh Industry-Specific Terms - Bayekeyeva, Ainur (Social Inclusion, 2021)
This article discusses the practical issues of compiling controlled multilingual thesauri for the purposes of industry-specific translation (IST). In the multilingual, transnational and globally connected Kazakhstan, IST is a much-needed translation service. IST is an interdisciplinary field between terminology, computational linguistics, translation theory and practice. Most of the professional guides, dictionaries and glossaries are systemized in alphabetical order and contain multiple variants for the terms searched. Therefore, there is an urgent need to create a systemized controlled multilingual thesaurus of industry-specific Kazakh, English and Russian terms in order to provide multilingual users with an interoperable and relevant term base. Controlled multilingual thesauri for industry-specific terms are the most effective tools for describing individual subject areas. They are designed to promote communication and interaction among professionals, translators and all Automated Information System users of specific fields irrespective of their location and health conditions. Unlike traditional dictionaries, controlled thesauri allow users to identify the meaning with the help of definitions and translations, relations of terms with other concepts, and broader and narrower terms. The purpose of this research is to unify and systematize industry-specific terms in Kazakh, to provide Russian and English equivalents, and to classify the terms into essential rubrics and subjects. Based on the Zthes data scheme to create a controlled multilingual thesaurus of industryspecific terms, the major rubrics have been formulated, and about 10,000 Kazakh mining and metal terms approved by the Terminological Committee of Kazakhstan have been structured.